2021
DOI: 10.3389/fcell.2021.675486
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Disruption of Phosphorylated Eukaryotic Initiation Factor-2α/Activating Transcription Factor 4/Indian Hedgehog Protects Intervertebral Disc Degeneration via Reducing the Reactive Oxygen Species and Apoptosis of Nucleus Pulposus Cells

Abstract: Excessive reactive oxygen species (ROS) and apoptosis in nucleus pulposus (NP) cells accelerate the process of intervertebral disc degeneration (IDD). Here, we integrated pathological samples and in vitro and in vivo framework to investigate the impact of phosphorylation of eukaryotic initiation factor-2α (eIF2α)/activating transcription factor 4 (ATF4)/Indian hedgehog (Ihh) signaling in the IDD. From the specimen analysis of the IDD patients, we found phosphorylated eIF2α (p-eIF2α), ATF4 and Ihh protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…The ISR, which is an important stress response, maintains homeostasis by downregulating global protein translation and upregulating the translation of stress-related proteins such as ATF4 13 . Our study showed that the proportion of p-eIF2α-positive cells was increased in degenerated disc tissues, which was consistent with a previous study 57 , proving that the ISR was activated in IDD. Although the ISR protects against adverse stimulation, its benefits to cells and tissues vary with duration and degree 13 , 58 .…”
Section: Discussionsupporting
confidence: 93%
“…The ISR, which is an important stress response, maintains homeostasis by downregulating global protein translation and upregulating the translation of stress-related proteins such as ATF4 13 . Our study showed that the proportion of p-eIF2α-positive cells was increased in degenerated disc tissues, which was consistent with a previous study 57 , proving that the ISR was activated in IDD. Although the ISR protects against adverse stimulation, its benefits to cells and tissues vary with duration and degree 13 , 58 .…”
Section: Discussionsupporting
confidence: 93%
“…The importance of hedgehog pathways in NP and AC homeostasis has been reported. Modulation of hedgehog pathways causes osteoarthritis ( Lin et al, 2009 ) and IVD degeneration in mice ( Bao et al, 2021 ). Gli1 has been found to be expressed in NP ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ATF4 expression can alleviate TNF-α-induced ROS production and apoptosis in NP cells ( 135 ). In addition, starvation-mediated TUNEL-positive frequency and apoptotic protein expression in AF cells can be significantly inhibited by PERK inhibitors ( 51 ).…”
Section: Ers May Become the Potential Therapeutic Target To Prevent I...mentioning
confidence: 99%